Effect of processing methods on the postharvest quality of cape gooseberry (Physalis peruviana L.) (2023)
ABSTRACT: The cape gooseberry (Physalis peruviana L.) is an exotic tropical fruit of great national and international importance due to its nutritional and organoleptic properties. The objective of this study was to evaluate different postharvest treatments—coating, vacuum impregnation, and immersion—on the conservation of several quality characteristics of cape gooseberry fruit. Moreover, the different conditions of the selected treatments were studied. Weight loss was assessed with a gravimetric analysis of the fresh and treated fruit. Firmness was determined by the instrumental texture. A sensory analysis was conducted using a multidimensional profile approach. Of the treatments evaluated, the lowest weight loss was recorded with the use of coating and immersion. However, the immersion process resulted in the product with the highest overall quality according to the sensory analysis and presented the most appropriate texture according to the firmness values. Finally, in the evaluation of the immersion, a significant influence of the CaCl2 immersion time (p < 0.05) on the firmness values of the product was found, resulting in longer times leading to less firm products. Considering 10% as a commercial standard limit for weight loss, the fruit treated under immersion and coating processes can be stored for at least 12 days. The immersion process is highlighted because it improved the sensory characteristics with respect to the control (i.e., without treatment). Therefore, it is a promising alternative for the postharvest treatment of cape gooseberries.